Development of portable digital spirometer using NI sbRIO - Ibrahim, Siti Noorjannah; Jusoh, Ahmad Zamani; Malik, N. Abd; Mazalan, S. (Institute of Electrical and Electronics Engineers Inc., 2018)
One of the effective ways to diagnose various respiratory diseases is using spirometry test. Good spirometer comes with excellent graphical user interface. Spirometer is used to measure lung parameters such as FVC (Forced Vital Capacity) and FEV1 (Forced Expiratory Volume in the first second). The aim of this project is to develop a portable spirometer using NI sbRIO FPGA board and LabVIEW Software. The LabVIEW program consists of two parts: 1) the data acquisition and 2) the disease diagnosis. The data acquisition part will obtain data from user in terms of breathed air. Meanwhile, the disease diagnosis part will use the obtained data to analyze the disease. The system uses National Instrument Single Board Rio 9636 (NI sbRIO) for digital data conversion and data acquisition and breathing hardware from which users will used to flow air into the spirometer. The breathing hardware uses Venturi’s principle where the difference of the two pressures with different tube diameters used to measure flow rate and volume of air exhaled over a period of time; to determine the respiratory conditions. Results obtained from three different volunteers with different health performances are also presented in this paper. The FEV1 ratio of a healthy volunteer is 81.1%, an asthma volunteer is 72.04%, while a volunteer with suspected bronchitis is 33.4%. Based on these results, unhealthy users tend to have smaller value of FEV1 with lower area under the curve when compared to a healthy user. The test results are represented in parameters of pulmonary functions which include Volume-time and Flowvolume graphs.